Castillo, G. y Soria, L. (2023). La ciudad desde la antropología: miradas etnográficas. Lima: Fondo Editorial de la Pontificia Universidad Católica del Perú, 404 pp. - Vega Romá, Pablo (2023)
La ciudad desde la antropología: miradas etnográficas is a book, edited by Gerardo Castillo and Laura Soria, which brings together a set of academic articles that provide a diverse reflection, at a thematic and methodological level, on anthropological debates around the city. This publication, which links in its chapters the analysis of the spatiality of the places addressed with the dynamics that constitute the social groups that inhabit them, represents a key contribution in the field of urban anthropology research